UZBEK LITERATURE OF THE 20TH CENTURY (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
Modern Uzbek literature becomes diverse, more daring in the choice of form and style. However, with the acquisition of creative freedom, the possibility of pluralism of opinions, there is a danger of the appearance of mediocre production. Uzbek literature of the 20th century absorbed both the national-epic traditions of artistic comprehension of being, and the neo-mythological ways of creating a textual world model, and the existential principle as one of the features of the modernist type of artistic consciousness. The trend of in-depth metaphorization and symbolization of the text, indicated already in the 90s, in order to create a certain, axiologically given, psychological atmosphere in the works of N. Eshonkulov, A.Atakhanov, T. Malik, U. Khamdam and other writers of Uzbek short stories of the end of the twentieth century can be predicted as one of the dominant ones in the development of Uzbek literature in the first quarter of the twenty-first century.